2014
DOI: 10.1021/jp502963w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation on the Gas Phase Reaction of Ethyl Formate with Cl Atoms

Abstract: The rate coefficient for the gas-phase reaction of Cl atoms with ethyl formate was measured over the temperature range of 268-343 K using relative rate methods, with ethyl chloride as a reference compound. The temperature dependent relative rate coefficients for the ethyl formate + Cl reaction were measured, and the modified Arrhenius expression kethyl formate(268-343) = (2.54 ± 0.57) × 10(-23) T(4.1) exp {-(981 ± 102)/T} cm(3) molecule(-1) s(-1) was obtained with 2σ error limits. The room temperature rate coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 26 publications
6
38
1
Order By: Relevance
“…The minimum energy path (MEP) was obtained by intrinsic reaction coordinate (IRC) calculations to verify that the transition state connects the designated local minima for the respective reactants and products. To improve the accuracy of calculated reaction energetics, single-point energy calculations were carried out for all the stationary points at M a n u s c r i p t 6 coupled-cluster with single and double and perturbative triple excitations (CCSD(T)) [20][21][22] combined with the correlation-consistent polarized valence triple-zeta (cc-pVTZ) [23] basis set method using the optimized geometries obtained at the M06-2X/6-31+G(d,p) level of theory…”
Section: Computational Methodologymentioning
confidence: 99%
“…The minimum energy path (MEP) was obtained by intrinsic reaction coordinate (IRC) calculations to verify that the transition state connects the designated local minima for the respective reactants and products. To improve the accuracy of calculated reaction energetics, single-point energy calculations were carried out for all the stationary points at M a n u s c r i p t 6 coupled-cluster with single and double and perturbative triple excitations (CCSD(T)) [20][21][22] combined with the correlation-consistent polarized valence triple-zeta (cc-pVTZ) [23] basis set method using the optimized geometries obtained at the M06-2X/6-31+G(d,p) level of theory…”
Section: Computational Methodologymentioning
confidence: 99%
“…[35][36][37]44 The ether functionality in CF 3 OCFQCF 2 thus appears responsible for an additional product channel, yet the proposed HF elimination route 8,9 is not expected to be dependent on the presence or absence of the oxygen atom.…”
Section: Discussionmentioning
confidence: 99%
“…The energies obtained for the above reactions are again in good agreement with analogous reactions described in the literature. 25,[34][35][36][37] The minor adduct, CF 3 OCF(OH)-C F 2 , has access to similar decomposition routes (see Fig. 3, see Fig.…”
Section: Oxidation Mechanismmentioning
confidence: 96%
“…The 6‐31 + G(d,p) was chosen because the same basis set was used for developing the model functional. Previous works have shown that the M06‐2X hybrid density functional provides reliable results for thermo chemistry and kinetics . The M06‐2X is a hybrid meta‐DFT method with a high percentage of HF exchange, and it has broadest applicability with average mean absolute errors of about 1.3, 1.2 and 0.5 kcal mol −1 , respectively, for thermochemical, barrier height and non‐covalent interaction calculations .…”
Section: Methodsmentioning
confidence: 99%